New Drug Repositioning Candidates for T-ALL Identified Via Human/Murine Gene Signature Comparison - Bonnet, Raphaël; Nebout, Marielle; Brousse, Carine; Reinier, Frédéric; Imbert, Véronique; Rohrlich, Pierre Simon; Peyron, Jean-François (Frontiers in Oncology, 2020)
T-cell Acute Lymphoblastic Leukemia (T-ALL) is an aggressive subtype of leukemia for which important progress in treatment efficiency have been made in the past decades to reach a cure rate of 75-80% nowadays. It is nevertheless mandatory to find new targets and active molecules for innovative therapeutic strategies as relapse is associated with a very dismal outcome. We designed an experimental workflow to highlight the conserved core pathways associated with leukemogenesis by confronting the gene expression profiles (GEPs) of human T-ALL cases to the GEP of a murine T-ALL representative model, generated by the conditional deletion of the PTEN tumor suppressor gene in T cell precursors (tPTEN-/-). We identified 844 differentially expressed genes, common GEPs (cGEP) that were conserved between human T-ALL and murine signatures, and also similarly differentially expressed, compared to normal T cells. Using bioinformatic tools we highlighted in cGEPan upregulation of E2F, MYC and mTORC1. Next, using Connectivity Map (CMAP) and CMAPViz a visualization procedure for CMAP data that we developed, we selected in silico three FDA-approved, bioactive molecule candidates: α-estradiol (α-E), nordihydroguaiaretic acid (NDGA) and prochlorperazine dimaleate (PCZ). At a biological level, we showed that the three drugs triggered an apoptotic cell death in a panel of T-ALL cell lines, activated a DNA damage response and interfered with constitutive mTORC1 activation and c-MYC expression. This analysis shows that the investigation of conserved leukemogenesis pathways could be a strategy to reveal new avenues for pharmacological intervention.